ANALISIS KEPUASAN MAHASISWA DALAM PEMBELAJARAN ONLINE DENGAN MENGGUNAKAN LMS MOODLE - Ilmadi Ilmadi; Elda Herlina; Isnurani Isnurani; Dede Muhtar Safari (STKIP Andi Matappa, 2021)
This study aims to see the level of student satisfaction in using Moodle as an online learning platform and to determine the independent variables that affect the level of student satisfaction. The type of this research is descriptive quantitative research with survey method, the object of this research are 531 students of Mathematics Study Program, FMIPA Pamulang University. The instrument used to collect data is Student Satisfaction Questionnaire towards online learning by using Moodle Learning Management System (LMS). Data analysis using correlation test. The results of this study are, the level of student satisfaction in using Moodle is high with an average of 74.70%, with a significant level of 0.01; adjusted for R2 the value of the four independent variables was obtained 0.383. While the multiple correlation analysis shows for each independent variable, namely gender 0.33; Age 0.06; experience using Moodle is 0.44 and for internet connection is 0.12 with the conclusion that the level of student satisfaction using Moodle is relatively high.